Assessing the Effect of Cassava Peel Flour as an Admixture on the Properties of Concrete. - Opiyo, Junior Ronney (Kabale University, 2024)
This research investigated the effect of Cassava Peel Flour (CPF) as an admixture on the properties of concrete. A chemical analysis was conducted on CPF, along with tests on the properties of coarse and fine aggregates. Concrete mix designs were prepared following the American Concrete Institute (ACI) method. Initial and final setting time tests were performed by incorporating CPF in varying proportions (0%, 1%, 2%, 3%, 4%, 5%, and 6%) by weight of cement. The results revealed that the addition of CPF delayed the setting time of the cement paste. As the CPF dosage increased, both the initial and final setting times were extended, with the highest delay at 6% CPF, showing an initial setting time of 150 minutes and a final setting time of 435 minutes, compared to 55 and 245 minutes, respectively, at 0% CPF. This demonstrates that CPF is an effective retarder. A consistency test was conducted using the same CPF dosages, resulting in consistencies ranging from 27.4% at 0% CPF to 63.1% at 6% CPF. The slump test for a design slump of 7.5 cm showed that slump values decreased slightly with increased CPF dosage immediately after mixing but increased 30 minutes after mixing, indicating CPF’s impact on workability over time. Compressive strength tests were conducted on cubes (150x150x150 mm) at 7, 14, and 28 days. At 7 days, compressive strength decreased with increasing CPF dosage, from 15.2 MPa at 0% CPF to 10.3 MPa at 6% CPF. However, at 14 and 28 days, compressive strength increased with CPF addition up to 2%, after which further CPF dosage resulted in a decrease in strength. This suggests that while small amounts of CPF can enhance compressive strength over time, excessive amounts may weaken the concrete.